Odpowiedź:
[tex]a) \: \frac{ - \sqrt{3} }{4} - \sqrt{3} = \frac{ - \sqrt{3} }{4} - \frac{4 \sqrt{3} }{4} = \frac{ - 5 \sqrt{3} }{4} \\ b) \: \frac{ \sqrt[3]{5} }{2} + 2 \sqrt[3]{5} = \frac{ \sqrt[3]{5} }{2} + \frac{4 \sqrt[3]{5} }{2} = \frac{5 \sqrt[3]{5} }{2} \\ c) \: \frac{25 \sqrt{10} - 15}{5} = \frac{5(5 \sqrt{10} - 3) }{5} = 5 \sqrt{10} - 3[/tex]
[tex]d) \: 2 \sqrt[3]{5} - 2(1 + \sqrt[3]{5} ) = 2 \sqrt[3]{5} - 2 - 2 \sqrt[3]{5} = - 2 \\ e) \: 10 - 4(2 - \sqrt{6} ) = 10 - 8 +4 \sqrt{6} = 2 + 4 \sqrt{6 } =2(1+2\sqrt{6} )\\ f) \: 3(1 - \sqrt[3]{ - 5} ) + 3 \sqrt[3]{5} = 3 + 3 \sqrt[3]{5} + 3 \sqrt[3]{5} = 3 + 6 \sqrt[3]{5} = 3(1 + 2 \sqrt[3]{5}) [/tex]